Family interview. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows the head of the family of four being interviewed after arriving at Santa Anita, California Assembly Center.